2021
DOI: 10.1038/s41598-021-85569-9
|View full text |Cite
|
Sign up to set email alerts
|

Gestational intermittent hyperoxia rescues murine genetic congenital heart disease in part

Abstract: Cardiac development is a dynamic process, temporally and spatially. When disturbed, it leads to congenital cardiac anomalies that affect approximately 1% of live births. Genetic variants in several loci lead to anomalies, with the transcription factor NKX2-5 being one of the largest. However, there are also non-genetic factors that influence cardiac malformations. We examined the hypothesis that hyperoxia may be beneficial and can rescue genetic cardiac anomalies induced by an Nkx2-5 mutation. Intermittent mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…In a murine model, hyperoxia therapy demonstrated the reduction of excess trabeculation and muscular ventricular septal defects and improved the organization of coronary vasculature in genetically modified mice [ 25 ]. A small study of 24 mothers with fetuses known to have CHD demonstrated a variable response to hyperoxygenation on cerebral tissue oxygenation [ 26 ].…”
Section: Maternal Hyperoxia Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In a murine model, hyperoxia therapy demonstrated the reduction of excess trabeculation and muscular ventricular septal defects and improved the organization of coronary vasculature in genetically modified mice [ 25 ]. A small study of 24 mothers with fetuses known to have CHD demonstrated a variable response to hyperoxygenation on cerebral tissue oxygenation [ 26 ].…”
Section: Maternal Hyperoxia Therapymentioning
confidence: 99%
“…The data presented in this study are openly available in reference number [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
unclassified